A Study of Bobwhite Quail Nest Initiation Dates, Clutch Sizes, and Hatch Sizes in Southwest Georgia - Ronald C. Simpson (National Quail Symposium Proceedings, 2017)
Nest initiation dates, size of clutches, and proportion of eggs hatching are presented for a high-density bobwhite quail (Colinus virginianus) population studied from 1967 through 1971 in southwest Georgia. Initiation dates were known for 680 nests that were active when found; of these, 379 nests (56%) were initiated before 16 June. Nesting success (percentage of all nests producing chicks) was low for these nests. Of 171 successful active nests with known initiation dates, only 38 (22%) were initiated before 16 June. Mean monthly clutch size decreased from March (25.0) to August (9.4). The mean clutch size for all nests was 12.0. The number of eggs hatching per nest also decreased from March (20.0) to August (8.4) with a mean of 9.9 eggs hatching for all nests.